Explicit solution for a class of coupled hyperbolic systems of conservation laws. Issue 3 (17th February 2021) - Sun, Wenhua; Liu, Yujin
ABSTRACT: Under suitably generalized Rankine–Hugoniot relation and entropy condition, by introducing a convex hull of potential function, the global explicit solution for the Cauchy problem to a class of coupled hyperbolic systems of conservation laws, which involves the piecewise initial value problem as a special case, is constructively obtained in the measure space.